2001
DOI: 10.1002/1521-3935(20010301)202:6<775::aid-macp775>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Thermal and Thermo-Oxidative Degradation of Polystyrene, Polyethylene and Poly(propylene)

Abstract: The thermal degradations of polystyrene (PS), polyethylene (PE), and poly(propylene) (PP) have been studied in both inert nitrogen and air atmospheres by using thermogravimetry and differential scanning calorimetry. The model‐free isoconversional method has been employed to calculate activation energies as a function of the extent of degradation. The obtained dependencies are interpreted in terms of degradation mechanisms. Under nitrogen, the thermal degradation of polymers follows a random scission pathway th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
400
1
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 672 publications
(460 citation statements)
references
References 43 publications
54
400
1
5
Order By: Relevance
“…Such was confirmed by Sanchez-Jimenez et al, proposing a random chain scission model (Sanchez-Jimenez et al , 2010, Sanchez-Jimenez et al , 2012. Since several authors have found that the activation energy does not change with the reacted fraction (Peterson et al , 2001, Sanchez-Jimenez et al , 2012, Snegirev et al , 2012, it can reasonably be assumed that the process is single step and other results can be a consequence of both inappropriate kinetic procedures or non-adequately controlled experimental conditions since it has been proved that heat and mass transfer phenomena can affect greatly to the calculated kinetic parameters.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Such was confirmed by Sanchez-Jimenez et al, proposing a random chain scission model (Sanchez-Jimenez et al , 2010, Sanchez-Jimenez et al , 2012. Since several authors have found that the activation energy does not change with the reacted fraction (Peterson et al , 2001, Sanchez-Jimenez et al , 2012, Snegirev et al , 2012, it can reasonably be assumed that the process is single step and other results can be a consequence of both inappropriate kinetic procedures or non-adequately controlled experimental conditions since it has been proved that heat and mass transfer phenomena can affect greatly to the calculated kinetic parameters.…”
Section: Introductionmentioning
confidence: 82%
“…An important volume of work has been devoted to the determination of the activation energy and kinetic model describing the thermal degradation of polystyrene (Brems et al , 2011, Chen et al , 2007, Chen and Vyazovkin, 2006, Faravelli et al , 2001, Peterson et al , 2001, Sanchez-Jimenez et al , 2012, Snegirev et al , 2012, Sterling et al , 2001, Westerhout et al , 1997. However, results show a wide divergence in the activation energy values and the kinetic models proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Estes resultados indicam que o processo de degradação termo-mecânica do poliestireno sob múltiplas extrusões reduz gradativamente a massa molar das cadeias, independentemente de seu comprimento (ou massa molar). Já é conhecido [17][18][19][20] que a degradação térmica do poliestireno a baixas temperaturas gera um mecanismo de cisão de cadeia aleatória, independente da massa molar da cadeia que está sendo degradada. Os dados deste trabalho mostram que este mecanismo também acontece na presença de cisalhamento, ou seja a degradação termo-mecânico também ocasiona a cisão das cadeias mas ela é independe cadeias clivadas por grama de amostra (n s ) esta na ordem de 10 17 e nas extrusões seguintes (x 4 e x 5) este valor aumenta para 10 18 cadeias clivadas por grama de PS.…”
Section: Distribuição De Cisão De Cadeia (Csdf)unclassified
“…Pode-se também encontrar outras equações que utilizam relações entre Peterson et al [20] estudaram a degradação térmica do poliestireno através da termogravimetria e calorimetria diferencial de varredura (DSC) sob atmosferas de nitrogênio e ar. Os autores observaram que a energia de ativação do PS sob atmosfera de nitrogênio é ≅ 48 kcal.mol -1 , no entanto, também observaram valores da energia de ≅ 36 kcal.mol -1 no estágio inicial da degradação e sugeriram que a degradação é iniciada por ligações lábeis.…”
Section: Introductionunclassified
“…Figure 4 shows TGA of the P(ST-co-ICPP) copolymer. The copolymer has lower thermal stability than is reported for polystyrene (PS) [24], the onset of decomposition at 221ºC (PS 350ºC), 10% weight loss at 287ºC (PS 425ºC), 50% weight loss at 362ºC (PS 428ºC). Lower thermal stability of the ST-ICPP copolymers apparently associated with presence of ICPP quaternary carbon in the chain similarly to poly-alpha-methylstyrene [25].…”
Section: Resultsmentioning
confidence: 93%